More than a bro: The semiotics of friendship in print advertisements - Zantides, Evripides (My University, 2025)
The semiotics of typography, images, and graphic design in print advertisements plays a crucial role in understanding how visual communication operates. Building on Williamson’s (2002) perspective, this paper considers advertisements not merely as vehicles for promoting the inherent qualities of a product or service but as meaning-making systems that resonate with culturally embedded ideas, desires, values, and beliefs. In this context, the study explores how friendship is constructed through the verbal and nonverbal signs of print advertising, with particular attention to how these representations foster human connection to cultivate brand loyalty. The research is based on a purposive corpus of global print advertisements from 2015 to 2025 by well-known brands, selected from advertising archives, and campaigns that depict friendship. Using semiotic analysis—drawing on Bertin’s (1967) theory on the semiology of graphics and Barthes’ tradition—the results reveal patterns of meaning-making aligned with values and relational dynamics of friendship.
Keywords: Semiotics, Typography, Graphic Design, Friendship, Advertising